Hubungan riwayat hipertensi, indeks massa tubuh dan usia ibu pada wanita hamil dengan kejadian preeklampsia di Rumah Sakit Kristen Mojowarno - Octavia, Helen; Siahaan, Salmon Charles Pardomuan Tua (Fakultas Kedokteran, Universitas Palangka Raya, 2023)
Preeclampsia is a multisystemic disorder in pregnant women with clinical hypertension, edema and accompanied by proteinuria. This research was conducted to determine the relationship between the risk factors for preeclampsia, such as old age, obesity, and a history of hypertension in pregnant women with the incidence of preeclampsia at Mojowarno Christian Hospital in 2020. This research was included in an observational analytic study with a case control study design based on medical record data at Mojowarno Christian Hospital in 2020 which was processed using the Chi Square statistical test method. The total sample of the study was 38 people with 19 people in each group. The results of this study indicate that a history of hypertension (p=0.005; OR=9.444) and body mass index >29 (p=0.027; OR=6.182) are risk factors for preeclampsia, while maternal age >35 years is not a risk factor for preeclampsia, because the results showed that maternal age >35 years was more common in pregnancies without preeclampsia than preeclampsia. Thus it can be concluded that there is a relationship between risk factors for history of hypertension and BMI > 29 and the incidence of preeclampsia and there is no relationship between risk factors for maternal age > 35 years and the incidence of preeclampsia in pregnant women at Mojowarno Christian Hospital in 2020.